A Evaluation Of The Frailty Index And Thiol-Disulphide Levels In Geriatric Orthopedic Injuries: Evaluation Of The Frailty Index - Işık, Hüseyin; Sahın Kavaklı, Havva; Silay, Kamıle (Scientific Reports in Medicine, 2024)
Backround: One of the concepts recently discussed about old age is frailty. Frailty was found to be important in determining weakness and indulgence in the elderly. Frail older people are more likely to fall and experience related orthopedic trauma. Free oxygen radicals are known to cause oxidative stress in trauma patients. The aim of this study is to report the levels of frailty and thiol disulphide homeostasis and related factors in patients with geriatric orthopedic injury who presented to the emergency department.Methods: This study included 82 patients aged 65 and over who were admitted to the Emergency Department of XXX City Hospital in 2020 due to orthopedic trauma, and 38 people who presented for other reasons in a control group. FRAIL Frailty scale was used to evaluate frailty. In samples from patients’ venous blood, native thiol and total thiol were analyzed.Results: The average age of the patients was78.48 ±7.86(min: 65-max: 99). Of the patients, 30.8% were in the prefrail group and56.7% were in the frail group. In patient and control group comparisons, total thiol values ​​in the patient group were significantly lower, and disulphide, ischemia-modified albumin, index 1 and index 2 values ​​were significantly higher in the patient group compared with the control group. There were significantly more prefrail individuals(41.5%) among orthopedic trauma patients, and frail individuals (81.6%) in the control group. There was a significant weak negative correlation between body mass index and native thiol and total thiol values.Conclusion: Oxidative stress is increased in patients with geriatric orthopedic injuries.